Features Of Formation Psychosocial Maladjustment In Women With Alopecia - Aymedov, C.; Zhyvylko, V. (Psychiatry, Neurology and Medical Psychology, 2016)
In the presented article the author shows theoretical foundation of a problem of organizing help to women suffering from baldness. The author analyzes the original and foreign literature on the problem of modern psychodermatology. The article analyzes maladaptive manifestation of the surveyed patients with alopecia, which occurred as the psycho-emotional and personal level, and the level of social functioning. The author considers the availability of psycho-emotional maladjustment (high neuroticism, aggression and hostility, anxiety, depression) as derivatives caused by distortion of personal characteristics.